Polar Patrol Balloon (PPB) experiment of the 30th Japanese Antarctic Research Expedition (1989-1990) - Akira Kadokura; Masaki Ejiri; Shigeo Ohta; Hiromitsu Akiyama (National Institute of Polar Research, 1991)
The 30th Japanese Antarctic Research Expedition (JARE-30) performed a Polar Patrol Balloon (PPB) experiment in January 1990. The launching date was January 5th. We could obtain position data until February 2nd and house keeping data until February 7th through ARGOS system. The trajectory of the PPB was about seven-eighth of a perfect circumpolar one. Auto-ballast system was normally operated to keep the flight level above 27km until 15 days after launch when all the ballast had been consumed, and then the balloon height became lower and lower. Before the ballast was completely consumed, the balloon drifted westward with a constant speed of about 18.7°per day by an easterly wind. After that the drifting speed gradually slowed down, eventually became zero on January 25th. On January 29th the balloon started drifting eastward. We calculated solar zenith angle and sunset angle at balloon height and found that the increase of ballast consumption began at the time when the maximum solar zenith angle became greater than a critical angle, in our case 92.4°. In order to understand the balloon drifting motion we referred to height profile data of zonal wind at Syowa Station during our flight. It was shown that when the balloon changed its drifting direction, the zonal wind direction was westerly at the balloon height.